RISKS AND PREVENTIVE MEASURES ON THE USE OF SOCIAL NETWORKS BY THE STUDENT WHO ATTENDS SECONDARY EDUCATION IN THE DISTRICT OF HORQUETAS, SARAPIQUÍ, HEREDIA, COSTA RICA - Schmidt-Fonseca, Ileana (2019)
The main objective of this research is to analyse the use of online social networks among the student body who takes secondary education, through the establishment of risks and preventive steps for a correct communication. The research was conducted under a quantitative approach with a explicative position. The population was formed by 1895 students, distributed in the III cycle of basic education and diversified education, from day high schools of the educative district 02, Sarapiquí canton, this is why it was opted to take a stratified statistic sample of 320 students.  As a result, it is determined that the 99% of the interviewees use electronic devices to communicate through internet, with a 96% the cellular phone. It is identified that 75% learnt only to use internet and a 95% uses social networks, a 96% whatsapp, 86% facebook, 67% Instagram, and a 31% snapchat. Moreover, it is evidenced that 83% of the students are alone when using social networks and only 33% of the educative institutions taught them about this topic. Apart from that, 80% of the parents do not establish controls on its use.  In conclusion, the student body of secondary uses mainly the cell phone to communicate and access social networks online, such as: Whatsapp, Facebook, and Instagram. In addition, it is established some differences on the relation to know and apply security and privacy policies on the use of those means of communication, it is shown  the lack of knowledge by the participants on the educative action: the teacher, student and parents, with regards to the risks and preventive steps when communicating through social networks.